2014
DOI: 10.1038/onc.2014.274
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181 family: regulators of myeloid differentiation and acute myeloid leukemia as well as potential therapeutic targets

Abstract: MicroRNAs have been shown to play an important role in normal hematopoisis and leukemogenesis. Here, we report function and mechanisms of miR-181 family in myeloid differentiation and acute myeloid leukemia (AML). The aberrant overexpression of all the miR-181 family members (miR-181a/b/c/d) was detected in French-American-British M1, M2 and M3 subtypes of adult AML patients. By conducting gain- and loss-of-function experiments, we demonstrated that miR-181a inhibits granulocytic and macrophage-like differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
127
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 50 publications
7
127
1
1
Order By: Relevance
“…The role for the different isoforms of CaM Kinases in oncogenesis is rapidly emerging and evidence supports the involvement for CaM KK, CaM KI, CaM KIV, CaM KII as well as their various substrates and cellular targets in cancer development [60,[68][69][70][71][72][73][74]. Consistent with our data, Iglewski et al demonstrated that urotensin treatment of primary smooth muscle cells activated a CaM KK/CaM KI/ERK proliferation pathway although the ability of other hormones to inhibit this process was not examined [75].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The role for the different isoforms of CaM Kinases in oncogenesis is rapidly emerging and evidence supports the involvement for CaM KK, CaM KI, CaM KIV, CaM KII as well as their various substrates and cellular targets in cancer development [60,[68][69][70][71][72][73][74]. Consistent with our data, Iglewski et al demonstrated that urotensin treatment of primary smooth muscle cells activated a CaM KK/CaM KI/ERK proliferation pathway although the ability of other hormones to inhibit this process was not examined [75].…”
Section: Resultssupporting
confidence: 81%
“…Similarly, recent data suggests that inhibiting CaM KK reduced both ERK and AKT activation as well as gastric cancer cell growth [76]. We did not evaluate the role of AKT or AMPK in our system although they may contribute to cell growth and survival downstream of CaM KK in several cancer cell types including breast, prostate, and myeloid [60,70,77,78]. Future studies may examine the specific effect that E2 has on AKT or AMPK activation and weather Vit D impairs their phosphorylation in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In acute myeloid leukemia (AML), upregulation of miR-181a was associated with a higher complete remission rate and better survival [63,64]. In other studies, inhibition of miR-181 family members reversed a differentiation block [65]. In chronic lymphocytic leukemia (CLL), a decrease in miR-181a expression is implicated in disease pathogenesis [66].…”
Section: Figmentioning
confidence: 99%
“…Hickey et al recently demon-strated that microRNA 181a (miRNA181a) is upregulated by the C/EBP␣ 30-kDa protein and functions as a tumor suppressor in the hematopoietic system (7). However, later studies demonstrated that this miRNA also has oncogenic activities in the myeloid background (8,9). Similar to miRNA181a, miRNA22 first was shown to display oncogenic activity (10), but further studies in several tissue culture systems and in vivo clearly demonstrated its tumor suppressor activities (11,12).…”
mentioning
confidence: 98%
“…The mechanisms of cancer-related elimination or reduction of tumor suppressor proteins include transcriptional repression of the genes, degradation of proteins, and posttranslational modifications that change biological activities of these proteins (1,3,4). A number of recent papers showed that certain proteins work as oncoproteins and as tumor suppressors depending on cell environment, target genes, and posttranslational modifications (5)(6)(7)(8)(9)(10)(11)(12). In this regard, Dreijerink et al have recently shown that menin tumor suppressor protein displays its tumor suppression activity in a variety of cancer cells; however, it possesses oncogenic activities in breast tumorigenesis (5).…”
mentioning
confidence: 99%